Addressing the plasmonic hotspot region by site-specific functionalization of nanostructures - Görlitzer, Eric; Speichermann, Lutz; Mirza, Talha Ahmed; Mohammadi, Reza; Vogel, Nicolas (Nanoscale Advances, 2020)
Strong electromagnetic fields emerge around resonant plasmonic nanostructures, focusing the light in tiny volumes, usually referred to as hotspots. These hotspots are the key regions governing plasmonic applications since they strongly enhance properties, signals or energies arising from the interaction with light. For a maximum efficiency, target molecules or objects would be exclusively placed within hotspot regions. Here, we propose a reliable, universal and high-throughput method for the site-specific functionalization of hotspot regions over macroscopic areas. We demonstrate the feasibility of the approach using crescent-shaped nanostructures, which can be fabricated using colloidal lithography. These structures feature polarization-dependent resonances and near-field enhancement at their tips, which we use as target regions for the site-selective functionalization. We modify the fabrication process and introduce a defined passivation layer covering the central parts of the gold nanocrescent, which, in turn, selectively uncovers the tips and thus enables a localized functionalization with thiol molecules. We demonstrate and visualize a successful targeting of the hotspot regions by binding small gold nanoparticles and show a targeting efficiency of 90%. Finally, we demonstrate the versatility of the method exemplarily by translating the principle to different nanostructure geometries and architectures.
CRIS-Team Scopus Importer:2020-02-04

Anisotropic silicon nanowire arrays fabricated by colloidal lithography - Rey, Marcel; Wendisch, Fedja J.; Görlitzer, Eric; Tang, Julia; Bader, Romina; Bourret, Gilles Remi; Vogel, Nicolas (Nanoscale Advances, 2021)
The combination of metal-assisted chemical etching (MACE) and colloidal lithography allows for the affordable, large-scale and high-throughput synthesis of silicon nanowire (SiNW) arrays. However, many geometric parameters of these arrays are coupled and cannot be addressed individually using colloidal lithography. Despite recent advancements towards higher flexibility, SiNWs fabricated via colloidal lithography and MACE usually have circular, isotropic cross-sections inherited from the spherical templates. Here we report a facile technique to synthesize anisotropic SiNWs with tunable cross-sections via colloidal lithography and MACE. Metal films with an elliptical nanohole array can form from shadows of colloidal particles during thermal evaporation of the metal at tilted angles. The aspect ratio of these anisotropic holes can be conveniently controlled via the deposition angle. Consecutive MACE using these patterned substrates with or without prior removal of the templating spheres results in arrays of anisotropic SiNWs with either elliptical or crescent-shaped cross-sections, respectively. As a consequence of the anisotropy, long SiNWs with elliptical cross-sections preferentially collapse along their short axis, leading to a controlled bundling process and the creation of anisotropic surface topographies. These results demonstrate that a rich library of SiNW shapes and mesostructures can be prepared using simple spherical colloidal particles as masks.
CRIS-Team WoS Importer:2021-05-28
Keywords: Hierarchical structures; Wettability; Absorption; Interfaces; Monolayers; Microgels; Diameter; Size

A Self‐Ordered Nanostructured Transparent Electrode of High Structural Quality and Corresponding Functional Performance - Döhler, Dirk; Triana Merlo, Andres Dario; Büttner, Pascal; Scheler, Florian; Görlitzer, Eric; Harrer, Johannes; Vasileva, Anna A.; Ali, Ezzeldin; Gruber, Wolfgang; Unruh, Tobias; Manshina, Alina A.; Vogel, Nicolas; et al. (Small, 2021)
The preparation of a highly ordered nanostructured transparent electrode based on a combination of nanosphere lithography and anodization is presented. The size of perfectly ordered pore domains is improved by an order of magnitude with respect to the state of the art. The concomitantly reduced density of defect pores increases the fraction of pores that are in good electrical contact with the underlying transparent conductive substrate. This improvement in structural quality translates directly and linearly into an improved performance of energy conversion devices built from such electrodes in a linear manne
Keywords: nanosphere lithography; anodic alumina; antimony sulfide

Bioinspired Photonic Pigments from Colloidal Self-Assembly - Görlitzer, Eric; Klupp Taylor, Robin; Vogel, Nicolas (Advanced Materials, 2018)
Keywords: structural color; photonic pigments; self-assembly; colloids; bioinspired

Chiral Plasmonic Shells: High-Performance Metamaterials for Sensitive Chiral Biomolecule Detection - Yang, Xiu; Huang, Shanshan; Chikkaraddy, Rohit; Görlitzer, Eric; Chen, Feiliang; Du, Jinglei; Vogel, Nicolas; Weiss, Thomas; Baumberg, Jeremy; Hu, Yidong (ACS Applied Materials and Interfaces, 2022)
Low-cost and large-area chiral metamaterials (CMs) are highly desirable for practical applications in chiral biosensors, nanophotonic chiral emitters, and beyond. A promising fabrication method takes advantage of self-assembled colloidal particles, onto which metal patches with defined orientation are created using glancing angle deposition (GLAD). However, using this method to make uniform and well-defined CMs over macroscopic areas is challenging. Here, we fabricate a uniform large-area colloidal particle array by interface-mediated self-assembly and precisely control the structural handedness of chiral plasmonic shells (CPSs) using GLAD. Strong chiroptical signals arise from twisted currents at the main, corner, and edge of CPSs, allowing a balance between strong chiroptical and high transmittance properties. Our shell-like chiral geometry shows excellent sensor performance in detecting chiral molecules due to the formation of uniform superchiral fields. Systematic investigations optimize the interplay between peak and null point resonances in different CPSs and result in a record consistency chiral sensor parameter U, i.e., 3.77 for null points and 0.0867 for peaks, which are about 54 and 1.257 times larger than the highest value (0.068) of previously reported CMs. The geometrical chirality, surface plasmonic resonance, chiral surface lattice resonance, and chiral sensor performance evidence the chiroptical effect and the excellent chiral sensor performance.
Keywords: chiral field; chiral metamaterials; chiral sensor; chiroptical effect; glancing angle deposition; microsphere self-assembly

Chiral Surface Lattice Resonances - Görlitzer, Eric; Mohammadi, Reza; Nechayev, Sergey; Volk, Kirsten; Rey, Marcel; Banzer, Peter; Karg, Matthias; Vogel, Nicolas (Advanced Materials, 2020)
Collective excitation of periodic arrays of metallic nanoparticles by coupling localized surface plasmon resonances to grazing diffraction orders leads to surface lattice resonances with narrow line width. These resonances may find numerous applications in optical sensing and information processing. Here, a new degree of freedom of surface lattice resonances is experimentally investigated by demonstrating handedness-dependent excitation of surface lattice resonances in arrays of chiral plasmonic crescents. The self-assembly of particles used as mask and modified colloidal lithography is applied to produce arrays of planar and 3D gold crescents over large areas. The excitation of surface lattice resonances as a function of the interparticle distance and the degree of order within the arrays is investigated. The chirality of the individual 3D crescents leads to the formation of chiral lattice modes, that is, surface lattice resonances that exhibit optical activity.
CRIS-Team Scopus Importer:2020-05-02
Keywords: chirality; colloidal lithography; optical activity; plasmonics; surface lattice resonances

Coloration in Supraparticles Assembled from Polyhedral Metal-Organic Framework Particles - Wang, Junwei; Liu, Yang; Bleyer, Gudrun; Peukert, Wolfgang; Görlitzer, Eric; Englisch, Silvan; Przybilla, Thomas; Mbah Chrameh, Fru; Engel, Michael; Spiecker, Erdmann; Imaz, Inhar; Maspoch, Daniel; et al. (Angewandte Chemie International Edition, 2022)
Supraparticles are spherical colloidal crystals prepared by confined self-assembly processes. A particularly appealing property of these microscale structures is the structural color arising from interference of light with their building blocks. Here, we assemble supraparticles with high structural order that exhibit coloration from uniform, polyhedral metal–organic framework (MOF) particles. We analyse the structural coloration as a function of the size of these anisotropic building blocks and their internal structure. We attribute the angle-dependent coloration of the MOF supraparticles to the presence of ordered, onion-like layers at the outermost regions. Surprisingly, even though different shapes of the MOF particles have different propensities to form these onion layers, all supraparticle dispersions show well-visible macroscopic coloration, indicating that local ordering is sufficient to generate interference effects.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Emulsion; Metal–Organic Frameworks; Self-Assembly; Structural Color; Supraparticles

How Colloidal Lithography Limits the Optical Quality of Plasmonic Nanohole Arrays - Görlitzer, Eric; Zhan, Meichen; Choi, Sukyung; Vogel, Nicolas (Langmuir, 2023)
Colloidal lithography utilizes self-assembled particle monolayers as lithographic masks to fabricate arrays of nanostructures by combination of directed evaporation and etching steps. This process provides complex nanostructures over macroscopic areas in a simple, convenient, and parallel fashion without requiring clean-room infrastructure and specialized equipment. The appeal of the method comes at the price of imperfections impairing the optical quality, especially for arrayed nanostructures relying on well-ordered lattices. Imperfections are often generically mentioned to rationalize the discrepancy between experimental and simulated resonances. Yet, little attention is given to detailed structure-property relationships connecting typical defects directly with the optical properties. Here, we use a correlative approach to connect nano- and microscopic defects occurring from the colloidal lithography process with the resulting local optical properties. We use nanohole arrays as a common plasmonic structure known to be sensitive to lattice imperfections. Correlative optical and electron microscopies reveal the individual role of packing order, organic impurities, and solid polymer bridges. Our findings show that simple cleaning processes with solvents and oxygen plasma already improve the optical quality but also highlight how well-controlled self-assembly processes are required for predictable optical properties of such nanostructures.
CRIS-Team Scopus Importer:2023-04-14

Large-Area 3D Plasmonic Crescents with Tunable Chirality - Görlitzer, Eric; Mohammadi, Reza; Nechayev, Sergey; Banzer, Peter; Vogel, Nicolas (Advanced Optical Materials, 2019)
Chiral plasmonic nanostructures hold promise for enhanced chiral sensing and circular dichroism spectroscopy of chiral molecules. It is therefore of interest to fabricate chiral plasmonic nanostructures with tailored chiroptical properties over large areas with reasonable effort. Here, a colloidal lithography approach is used to produce macroscopic arrays of sub-micrometer 3D chiral plasmonic crescent structures over areas >1 cm 2 . The chirality originates from symmetry breaking by the introduction of a step within the crescent structure. This step is produced by an intermediate layer of silicon dioxide onto which the metal crescent structure is deposited. It is experimentally demonstrated that the chiroptical properties in such structures can be tailored by changing the position of the step within the crescent. These experiments are complemented by finite element simulations and the application of a multipole expansion to elucidate the physical origin of the circular dichroism of the crescent structures.
CRIS-Team Scopus Importer:2019-06-04
Keywords: chirality; colloidal lithography; multipole decomposition; plasmonics; split-ring resonator

Molecular-Induced Chirality Transfer to Plasmonic Lattice Modes - Görlitzer, Eric; Zapata-Herrera, Mario; Ponomareva, Ekaterina; Feller, Déborah; Garcia-Etxarri, Aitzol; Karg, Matthias; Aizpurua, Javier; Vogel, Nicolas (ACS Photonics, 2023)
Molecular chirality plays fundamental roles in biology. The chiral response of a molecule occurs at a specific spectral position, determined by its molecular structure. This fingerprint can be transferred to other spectral regions via the interaction with localized surface plasmon resonances of gold nanoparticles. Here, we demonstrate that molecular chirality transfer occurs also for plasmonic lattice modes, providing a very effective and tunable means to control chirality. We use colloidal self-assembly to fabricate non-close packed, periodic arrays of achiral gold nanoparticles, which are embedded in a polymer film containing chiral molecules. In the presence of the chiral molecules, the surface lattice resonances (SLRs) become optically active, i.e., showing handedness-dependent excitation. Numerical simulations with varying lattice parameters show circular dichroism peaks shifting along with the spectral positions of the lattice modes, corroborating the chirality transfer to these collective modes. A semi-analytical model based on the coupling of single-molecular and plasmonic resonances rationalizes this chirality transfer. © 2023 The Authors. Published by American Chemical Societ
Keywords: chirality transfer; nanoparticles; chirality; nanophotonics; surface lattice resonances

N-Methyl-2-pyrrolidone as a Reaction Medium for Gold(III)-Ion Reduction and Star-like Gold Nanostructure Formation - Mirdamadi Esfahani, Maleknaz; Görlitzer, Eric; Kunz, Ulrike; Vogel, Nicolas; Engstler, Joerg; Andrieu-Brunsen, Annette (ACS Omega, 2022)
The efficiency of a wet chemical route to synthesize gold nanostructures with tunable size and shape significantly depends on the applied solvent and the interaction of solvent molecules with other species such as gold ions. The ability of the organic solvent N-methyl-2-pyrrolidone (NMP) as a suitable medium for application in star-like gold nanostructure (AuNS) synthesis with a tunable morphology at ambient conditions has been investigated. The time-dependent analysis of the UV-vis absorption spectra of AuIIICl4- in a pure NMP solution illustrates the role of NMP as simultaneous complexing and reducing agents. Kinetic studies indicate that AuIIICl4- in NMP solution is reduced to AuICl2-, with no need to use another reducing agent, any external energy sources, or solvent pretreatment. This is because AuI species stay stable in this solution unless poly(vinylpyrrolidone) (PVP) catalyzes their disproportionation. Morphological studies by transmission electron microscopy (TEM) specify the high-yield synthesis of AuNS with monocrystalline spikes in a concentrated NMP solution by PVP. This study illustrates that the presence of seeds, as another agent to catalyze the disproportionation of AuI species, makes it possible to synthesize AuNS in varying concentrations of PVP in this medium. The role of PVP concentration and the presence of seeds in the formation kinetics, morphology, and optical properties is systematically discussed. The results achieved through this study develop a straightforward and safe procedure for AuNS synthesis in high yield in a water-miscible organic polar solvent with tunable morphology and optical properties. Considering the high capability of NMP to dissolve various types of polymers and hydrophobic ligands, synthesizing AuNS in this solvent opens a window to a practical and easy way to fabricate gold-based nanomaterials with fascinating optical properties.
Created from Fastlane, Scopus look-up

Quantitative Optical and Structural Comparison of 3D and (2+1)D Colloidal Photonic Crystals - Römling, Lukas; Bleyer, Gudrun; Görlitzer, Eric; Onishchukov, Georgy; Vogel, Nicolas (Langmuir, 2023)
Colloidal crystals are excellent model systems to study self-assembly and structural coloration because their periodicities coincide with the wavelength range of visible light. Different assembly methods inherently introduce characteristic defects and irregularities, even with nearly monodisperse colloidal particles. Here, we investigate how these imperfections influence the structural coloration by comparing two techniques to obtain colloidal crystals. 3D colloidal crystals produced by convective assembly are well-ordered and periodically arranged but show microscopic cracks. (2+1)D colloidal crystals fabricated by stacking individual monolayers show a decreased hexagonal order and limited crystal registration between single monolayers in the z-direction. We investigate the optical properties of both systems by comparing identical numbers of layers using correlative microspectroscopy. These measurements show that the less ordered (2+1)D colloidal crystals exhibit higher reflected light intensities. Macroscopic reflection integrating all angles shows that the reflected light intensity levels out with an increasing number of layers, whereas incoherent scattering increases. Although both types of colloidal crystal show similar angle-dependent color shifts in specular reflection, the less-ordered structure of the (2+1)D colloidal crystal scatters light within a larger angular range under diffusive illumination. Our results suggest that structural coloration is surprisingly robust toward local defects and irregularities.
CRIS-Team Scopus Importer:2023-04-14

Self-Assembled Au Nanoparticle Monolayers on Silicon in Two- and Three-Dimensions for Surface-Enhanced Raman Scattering Sensing - Bartschmid, Theresa; Farhadi, Amin; Musso, Maurizio E.; Görlitzer, Eric; Vogel, Nicolas; Bourret, Gilles R. (ACS Applied Nano Materials, 2022)
Gold nanoparticle/silicon composites are canonical substrates for sensing applications because of their geometry-dependent physicochemical properties and high sensing activity via surface-enhanced Raman spectroscopy (SERS). The self-assembly of gold nanoparticles (AuNPs) synthesized via wet-chemistry on functionalized flat silicon (Si) and vertically aligned Si nanowire (VA-SiNW) arrays is a simple and cost-effective approach to prepare such substrates. Herein, we report on the critical parameters that influence nanoparticle coverage, aggregation, and assembly sites in two- and three-dimensions to prepare substrates with homogeneous optical properties and SERS activity. We show that the degree of AuNP aggregation on flat Si depends on the silane used for the Si functionalization, while the AuNP coverage can be adjusted by the incubation time in the AuNP solution, both of which directly affect the substrate properties. In particular, we report the reproducible synthesis of nearly touching AuNP chain monolayers where the AuNPs are separated by nanoscale gaps, likely to be formed due to the capillary forces generated during the drying process. Such substrates, when used for SERS sensing, produce a uniform and large enhancement of the Raman signal due to the high density of hot spots that they provide. We also report the controlled self-assembly of AuNPs on VA-SiNW arrays, which can provide even higher Raman signal enhancement. The directed assembly of the AuNPs in specific regions of the SiNWs with a control over NP density and monolayer morphology (i.e., isolated vs nearly touching NPs) is demonstrated, together with its influence on the resulting SERS activity.
CRIS-Team Scopus Importer:2022-09-09
Keywords: Au nanoparticles; metal-assisted chemical etching; plasmonics; self-assembly; SERS; silicon nanowires

Spatioselective Deposition of Passivating and Electrocatalytic Layers on Silicon Nanowire Arrays. - Wendisch, Fedja J.; Abazari, Mehri; Werner, Valerie; Barb, Horia; Rey, Marcel; Görlitzer, Eric; Vogel, Nicolas; Mahdavi, Hossein; Bourret, Gilles R. (ACS Applied Materials and Interfaces, 2020)
Metal–silicon nanowire array photoelectrodes provide a promising architecture for water-splitting because they can afford high catalyst loading and decouple charge separation from the light absorption process. To further improve and understand these hybrid nanowire photoelectrodes, control of the catalyst amount and location within the wire array is required. Such a level of control is currently synthetically challenging to achieve. Here, we report the synthesis of cm2-sized hybrid silicon nanowire arrays with electrocatalytically active Ni–Mo and Pt patches placed at defined vertical locations within the individual nanowires. Our method is based on a modified three-dimensional electrochemical axial lithography (3DEAL), which combines metal-assisted chemical etching (MACE) to produce Si nanowires with spatially defined SiO2 protection layers to selectively cover and uncover specific areas within the nanowire arrays. This spatioselective SiO2 passivation yields nanowire arrays with well-defined exposed Si surfaces, with feature sizes down to 100 nm in the axial direction. Subsequent electrodeposition directs the growth of the metal catalysts at the exposed silicon surfaces. As a proof of concept, we report photoelectrocatalytic activity of the deposited catalysts for the hydrogen evolution reaction on p-type Si nanowire photocathodes. This demonstrates the functionality of these hybrid metal/Si nanowire arrays patterned via 3DEAL, which paves the way for investigations of the influence of three-dimensional geometrical parameters on the conversion efficiency of nanostructured photoelectrodes interfaced with metal catalysts.
Keywords: Metals; Nanowires; Nanowire arrays; Catalysts; Deposition

Structural Color of Colloidal Clusters as a Tool to Investigate Structure and Dynamics - Wang, Junwei; Sultan, Umair; Görlitzer, Eric; Mbah Chrameh, Fru; Engel, Michael; Vogel, Nicolas (Advanced Functional Materials, 2019)
Colloidal assemblies have applications as photonic crystals and templates for functional porous materials. While there has been significant progress in controlling colloidal assemblies into defined structures, their 3D order remains difficult to characterize. Simple, low-cost techniques are sought that characterize colloidal structures and assist optimization of process parameters. Here, structural color is presented to image the structure and dynamics of colloidal clusters prepared by a confined self-assembly process in emulsion droplets. It is shown that characteristic anisotropic structural color motifs such as circles, stripes, triangles, or bowties arise from the defined interior grain geometry of such colloidal clusters. The optical detection of these motifs reliably distinguishes icosahedral, decahedral, and face-centered cubic colloidal clusters and thus enables a simple yet precise characterization of their internal structure. In addition, the rotational motion and dynamics of such micrometer-scale clusters suspended in a liquid can be followed in real time via their anisotropic coloration. Finally, monitoring the evolution of structural color provides real-time information about the crystallization pathway within the confining emulsion droplet. Together, this work demonstrates that structural color is a simple and versatile tool to characterize the structure and dynamic properties of colloidal clusters.
CRIS-Team Scopus Importer:2019-11-26
Keywords: colloidal clusters; confinement; crystallization; self-assembly; structural color; supraparticles

Surface Patterning with SiO2@PNiPAm Core–Shell Particles - Tang, Jo Sing; Bader, Romina Sigrid; Görlitzer, Eric; Wendisch, Jan Fedja; Bourret, Gilles Remi; Rey, Marcel; Vogel, Nicolas (ACS Omega, 2018)
Colloidal lithography is a cost-efficient method to produce large-scale nanostructured arrays on surfaces. Typically, colloidal particles are assembled into hexagonal close-packed monolayers at liquid interfaces and deposited onto a solid substrate. Many applications, however, require non close-packed monolayers, which are more difficult to fabricate. Preassembly at the oil/water interface provides non close-packed colloidal assemblies but these are difficult to transfer to a solid substrate without compromising the ordering due to capillary forces acting upon drying. Alternatively, plasma etching can reduce a close-packed monolayer into a non close-packed arrangement, however, with limited interparticle distance and compromised particle shape. Here, we present a simple alternative approach toward non close-packed colloidal monolayers with tailored interparticle distance, high order, and retained spherical particle shape. We preassemble poly(N-isopropylacrylamide)-silica (SiO2@PNiPAm) core–shell particles at the air/water interface, transfer the interfacial spacer to a solid substrate, and use the polymer shell as a sacrificial layer that can be thermally removed to leave a non close-packed silica monolayer. The shell thickness, cross-linking density, and the phase behavior upon compression of these complex particles at the air/water interface provide parameters to precisely control the lattice spacing in these surface nanostructures. We achieve hexagonal non close-packed arrays of silica spheres with interparticle distances between 400 and 1280 nm, up to 8 times their diameter. The retained spherical shape is advantageous for surface nanostructuring, which we demonstrate by the fabrication of gold nanocrescent arrays via colloidal lithography and silicon nanopillar arrays via metal-assisted chemical etching.<br

The Beginner's Guide to Chiral Plasmonics: Mostly Harmless Theory and the Design of Large-Area Substrates - Görlitzer, Eric; Puri, Aniket S.; Moses, Jebin J.; Poulikakos, Lisa V.; Vogel, Nicolas (Advanced Optical Materials, 2021)
Chiral plasmonics is a fascinating research field that is attractive to scientists from diverse backgrounds. Physicists study light–matter interactions, chemists seek ways to analyze enantiomeric molecules, biologists study living objects, and material engineers focus on scalable production processes. Successful access to this emergent field for an interdisciplinary community depends on overcoming three main issues. First, understanding the physical background of chiral plasmonics requires proper introduction in easy language. Second, pitfalls in the characterization of chiroplasmonic features can prevent accurate interpretation. Third, simple and robust methods capable of covering macroscopic substrate areas must be available. This tutorial-style review addresses these issues with the goal to provide a comprehensive introduction into chiral plasmonic nanostructures. It starts with a brief introduction of the relevant physics involved in chiral light−matter interactions. A brief guide about how to adequately characterize samples follows. Subsequently, an overview of fabrication techniques that produce chiral substrates over large areas is given, and the strengths and weaknesses of the different approaches are discussed. The focus is on simple and robust processes that do not require clean room facilities and can be implemented by a much larger scientific audience.
Created from Fastlane, Scopus look-up
Keywords: chirality; colloidal lithography; large-area substrates; plasmonics; surface patterning

Ultrasensitive Ultraviolet Chiral Plasmonic Biosensor Based on Passivated Al Shells - Huang, Shanshan; Wang, Siyi; Yang, Xiu; Görlitzer, Eric; Peng, Jialong; Liu, Zhuang; Chikkaraddy, Rohit; Du, Jinglei; Vogel, Nicolas; Hou, Yidong (ACS Applied Materials and Interfaces, 2025)
Chiroptical spectroscopic techniques offer a nondestructive means of elucidating the stereochemical structures of biomolecules and have demonstrated significant applications across diverse fields, including bioscience, biomedicine, and clinical diagnosis, among others. However, the inherently weak chiroptical effects exhibited by natural chiral molecules pose a significant challenge to detection sensitivity. In this study, we demonstrate an ultrasensitive ultraviolet chiral plasmonic biosensor (CPB) that leverages a self-assembled metasurface composed of passivated aluminum chiral shells (ACSs). By meticulously optimizing the geometry and size of these shells, we achieve a uniform, large, and readily accessible superchiral field on the top surface of the ACSs, thereby enhancing their interaction with chiral biomolecules. In addition, the abundant surface lattice resonance (SLR) modes excited in the ultraviolet waveband narrow the chiroptical resonance peaks and improve the identifiability of sensor pointers. In experiments, large-area ACSs with strong chiroptical effects were realized by depositing Al on a colloidal monolayer with hexagonal order and then passivating it with ozone to improve stability. When immersed in solutions containing chiral molecules, the g-factor maxima of the ACSs exhibit a notable peak shift that correlates with both the stereochemical structures and the concentrations of the biomolecules. Notably, the consistency chiral sensor parameter U reaches 10.9095 for the null point and 0.1739 for peaks of g-factor spectra, which makes a record in the field CPBs. The systematic analysis of the SLR modes, superchiral field, and chiral sensor parameters further rationalizes the record chiral sensor performance realized in this work.
CRIS-Team Scopus Importer:2025-05-09
Keywords: chiral biosensor; chiral field; chiroptical effect; glancing angle deposition; microsphere lithography; ultraviolet chiral metamaterials